2022
DOI: 10.1128/spectrum.00950-22
|View full text |Cite
|
Sign up to set email alerts
|

Hibifolin, a Natural Sortase A Inhibitor, Attenuates the Pathogenicity of Staphylococcus aureus and Enhances the Antibacterial Activity of Cefotaxime

Abstract: We identified hibifolin as a sortase A (SrtA) inhibitor by screening the natural compounds library, which effectively inhibited the activity of SrtA with an IC 50 value of 31.20 μg/mL. Hibifolin attenuated the pathogenic behavior of Staphylococcus aureus , including adhesion, invasion, and biofilm formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Based on the obtained results, we suggested that the studied bioactive compounds could inhibit the activity of the SrtA enzyme by binding to its active site. Similar findings were demonstrated by another in silico study, which displayed that hibifolin attenuated the pathogenicity of S. aureus by inhibiting SrtA activity at free energy of binding equal to −6.8 Kcal/mol [ 58 ]. The interaction profiles representing the binding mode of the tested molecules against the selected bacterial virulence factors active sites are elucidated in Figure 3 , Figure 4 , Figure 5 and Figure 6 , and all the interaction details are summarized in Table 1 .…”
Section: Resultssupporting
confidence: 86%
“…Based on the obtained results, we suggested that the studied bioactive compounds could inhibit the activity of the SrtA enzyme by binding to its active site. Similar findings were demonstrated by another in silico study, which displayed that hibifolin attenuated the pathogenicity of S. aureus by inhibiting SrtA activity at free energy of binding equal to −6.8 Kcal/mol [ 58 ]. The interaction profiles representing the binding mode of the tested molecules against the selected bacterial virulence factors active sites are elucidated in Figure 3 , Figure 4 , Figure 5 and Figure 6 , and all the interaction details are summarized in Table 1 .…”
Section: Resultssupporting
confidence: 86%
“…It attenuates the virulence of both MSSA and MRSA strains in vitro and in vivo. As with other sortase A inhibitors tested in murine models of S. aureus infections [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ], LPRDA may impact the development of novel antibacterial agents. The pure crystalline form of LPRDA is characterized by good solubility and tolerance to eukaryotic and bacterial cells at working concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Computational drug engineering, for instance, identified 3,6-disubstituted triazolothiadiazole as a potent inhibitor of sortase A that improved infection outcomes of lethal S. aureus bacteremia ( Table 1 ; Zhang et al, 2014 ). Further, compound library screening helped to isolate several natural products with sortase A-blocking and anti-infective properties ( Table 1 ; Song et al, 2022a , b ). Some of these agents even potentiated the efficacy of cell wall biosynthesis-targeting antibiotics during experimental pneumonia, presumably aiding in the design of poly-therapeutic approaches that may also encompass usage of allantodapsone, a prototype pan-inhibitor of staphylococcal adhesion to extracellular matrix proteins ( Prencipe et al, 2022 ), to combat complicated MRSA infections in the future ( Table 1 ; Song et al, 2022a , b ; Wang et al, 2022b ).…”
Section: Targeting Cell Surface Proteins and Sortase A To Improve ...mentioning
confidence: 99%